Teachers and students perceptions of teaching English in small classes in Ecuador, estudio realizado en la escuela particular Academia Militar del Valle del cantón Quito, provincia de Pichincha, en el año lectivo 2013-2014 - Domínguez Leiva, Jacqueline Randy (2014)
This research is about Teachers and students perceptions of teaching English in small classes in Ecuador . Its purpose is to know the possible teaching benefits, strategies and resources used, students feelings, and probable limitations when teaching English in small classes. The study was carried out in Academia Militar del Valle which is a private school located in Quito-Ecuador. The methods applied in this study were quantitative and qualitative; the instruments used were students and teachers questionnaires and observational sheets. The participants were 5 EFL teachers and 94 students across five secondary classrooms selected. The data gathered from the questionnaires was correlated with the information registered in the observation sheets and the literature review. The results revealed that the main benefits of teaching and learning English in small classes were that there were more opportunities of teacher-student interaction, better students concentration but this did not ensure the participation of all students, proper feedback provided, and the existence of a good rapport. Moreover, the teachers tended to use a whole class instruction with an increasing of individual work and less pair work.